2017
DOI: 10.1111/cdev.12794
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adolescents’ Bullying Participation from Developmental Trajectories of Social Status and Behavior

Abstract: The aim of this study was to determine how trajectory clusters of social status (social preference and perceived popularity) and behavior (direct aggression and prosocial behavior) from age 9 to age 14 predicted adolescents' bullying participant roles at age 16 and 17 (n = 266). Clusters were identified with multivariate growth mixture modeling (GMM). The findings showed that participants' developmental trajectories of social status and social behavior across childhood and early adolescence predicted their bul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 88 publications
(143 reference statements)
3
35
2
3
Order By: Relevance
“…A longitudinal study conducted by Pouwels et al. () showed developmental trajectories of social status and behavior and that these trajectories predicted involvement in different bullying roles in adolescents. However, bullying was analyzed as a distal outcome and bullying trajectories were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study conducted by Pouwels et al. () showed developmental trajectories of social status and behavior and that these trajectories predicted involvement in different bullying roles in adolescents. However, bullying was analyzed as a distal outcome and bullying trajectories were not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies described in Table 1 showed that perpetration at one time point was usually related to perpetration at another time point (and vice versa for victimization), but transitions were not reported. A longitudinal study conducted by Pouwels et al (2018) showed developmental trajectories of social status and behavior and that these trajectories predicted involvement in different bullying roles in adolescents. However, bullying was analyzed as a distal outcome and bullying trajectories were not reported.…”
Section: Stability and Change In Bullying Rolesmentioning
confidence: 99%
“…In a similar vein, a recent large‐scale field study showed that interventions aimed at changing perceptions in the peer group can effectively reduce overall levels of conflict in schools (Paluck, Shepherd, & Aronow, ). One of the key motivations behind bullying is a possible increase in status for the bullies (Caravita & Cillessen, ; Juvonen & Galván, ; Pellegrini & Long, ; Pouwels et al., ; Salmivalli & Peets, ; Sijtsema, Veenstra, Lindenberg, & Salmivalli, ). Considering the key role peers have in stopping or maintaining bullying, a bully's pursuit of status in the peer group may be more successful in peer groups with more positive perceptions of bullies.…”
mentioning
confidence: 99%
“…Tal relação também foi encontrada em pré-escolares, como no estudo de Camodeca, Caravita & Coppola, (2015) com crianças entre 3 a 6 anos de idade; em crianças escolares, como no estudo Jia e Mikami (2015) onde o alto comportamento externalizante e junto com a presencia de baixa preferência social previam a classificação como agressor no bullying em crianças de 6 a 9 anos de idade; e em adolescentes escolares, como o estudo de Palacios e Berger (2016) no qual se demostrou correlação negativa entre ser agressor(bullying) e preferência social, mas só para os meninos, em escolares chilenos do 6º e 7º ano. Não obstante, alguns estudos têm em população adolescente comprovado que seus agressores apresentaram preferência social média (i. e. Pouwels et al, 2017).…”
Section: Descobertas Sobre a Preferência Socialunclassified
“…(Berger & Caravita, 2016;de Bruyn, Cillessen & Wissink, 2010;Palacios & Berger, 2016;Peeters et al, 2010 ;Pouwels, et al, 2017). Mas ao contrário do esperado a partir da literatura anterior (i. e. Bruyn et al, 2010), no presente estudo não encontramos correlação negativa entre popularidade percebida e vitimização.…”
Section: Descobertas Sobre a Popularidade Percebidaunclassified